2019
DOI: 10.5267/j.msl.2019.5.032
|View full text |Cite
|
Sign up to set email alerts
|

Financial performance and corporate social responsibility in the banking sector of Bahrain: Can engagement moderate?

Abstract: The present study attempted to understand how financial performance can be enhanced in the financial sector. Therein, the study worked to find out how Corporate Social Responsibility (CSR) and organizational engagement can be used to predict financial performance. In addition, the study also tested the moderating role of organizational engagement on the relationship between CSR and financial performance. Managerial level employees from seven retail banks in Bahrain were sampled for the present study. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 53 publications
1
38
1
Order By: Relevance
“…The few explored mediating variables are invested time on task (Stoeber, Chesterman, & Tarn, 2010), perceived pressure to be perfect (Stoeber& Renner, 2008) and achievement goals (Stoeber et al, 2015). However, in the present research, work motivation has been employed as a mediator that cause perfectionist striving and performance relationship because Stoeber, (2013) argued that work motivation is a variable that elaborate the positive association of perfectionism with workaholism and other positive work behaviors because perfectionists always work with determination and motivation which in turn leads towards positive performance (Galdeano, Ahmed, Fati, Rehan & Ahmed, 2019). This argument has been further strengthen by other researchers (Hall, Hill, & Appleton, 2012;Mills & Blankstein, 2000;Stoeber, Feast, &Hayward, 2009;Van Yperen, 2006) who have confirmed the significant positive association of perfectionist striving with motivation and all types (introjected regulation, identified regulation, intrinsic motivation and extrinsic motivation) proposed by self-determination theory (SDT), suggesting that perfectionist are highly motivated through the variety of motivations.…”
Section: Overview Of the Conceptsmentioning
confidence: 98%
See 1 more Smart Citation
“…The few explored mediating variables are invested time on task (Stoeber, Chesterman, & Tarn, 2010), perceived pressure to be perfect (Stoeber& Renner, 2008) and achievement goals (Stoeber et al, 2015). However, in the present research, work motivation has been employed as a mediator that cause perfectionist striving and performance relationship because Stoeber, (2013) argued that work motivation is a variable that elaborate the positive association of perfectionism with workaholism and other positive work behaviors because perfectionists always work with determination and motivation which in turn leads towards positive performance (Galdeano, Ahmed, Fati, Rehan & Ahmed, 2019). This argument has been further strengthen by other researchers (Hall, Hill, & Appleton, 2012;Mills & Blankstein, 2000;Stoeber, Feast, &Hayward, 2009;Van Yperen, 2006) who have confirmed the significant positive association of perfectionist striving with motivation and all types (introjected regulation, identified regulation, intrinsic motivation and extrinsic motivation) proposed by self-determination theory (SDT), suggesting that perfectionist are highly motivated through the variety of motivations.…”
Section: Overview Of the Conceptsmentioning
confidence: 98%
“…These are need for autonomy (i.e., possessing a sense of freedom), need for competence (i.e., a sense of feeling own self capable and effective) and need for relatedness (i.e., feeling loved and cared) (p: 981). According to Ryan and Deci (2003), self-determination theory is developmental for all humans because goals, values and behaviors can be integrated, connected or organized within one's own self (Galdeano, Ahmed, Fati, Rehan & Ahmed, 2019).…”
Section: Moderating Role Of Basic Psychological Needsmentioning
confidence: 99%
“…Banking sector has attracted significant scholarly attention over the past few decades (Galdeano, Ahmed, Fati, Rehan & Ahmed, 2019;Umrani, Kura & Ahmed, 2018;Umrani, Mahmood & Ahmed, 2016;Khalid, Pahi & Ahmed, 2016). Therein, debt financing comprises of main sources of external funding for most banks.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Most of the studies found in the literature (Parker & Ameen, 2018;Sutcliffe and Vogus, 2003) suggest the implications and outcomes of organizational resilience during the crisis. Very limited attention has been paid so far towards the actions that create resilience in organizations (Galdeano, Ahmed, Fati, Rehan & Ahmed, 2019;Ishak & Williams, 2018). One of the antecedents of organizational resilience is strategic human resource management (SHRM) as suggested by (Stokes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%